Chapter 16 Cloud Backup and Restore The Infrastructure of Digital Failure - Taylor, A.R.E (Taylor & Francis, 2023)
Digital devices are prone to failure. An increasing range of cloud backup solutions aim to ensure that no matter what should happen to a user's device, their files and data can be quickly re-downloaded and re-installed on a new device with ease. If the failure or breakdown of a digital device may once have resulted in a potentially devastating data loss event, cloud backup and recovery tools work to reduce the disruptive impact of device failure. This has implications for theories of failure that are based on the premise that breakdown or failure are disruptive events. Drawing on Apple's cloud-based data backup and restore service, this chapter conceptualises the cloud as an infrastructure designed to anticipate and absorb digital failure. In doing so, it explores how cloud services bolster cultures of routine device upgrading and e-waste production.